IDENTIFIKASI PENYAKIT PADA TANAMAN PADI DI KELURAHAN OESAO, KABUPATEN KUPANG, NUSA TENGGARA TIMUR - Simamora, Agnes V; Hahuly, Mayavira V; Ishaq, Lily F; Nenotek, Petronella S; Ola, Antonius R B; Hosang, Evert Y; Fitriadi, Bayu Refindra (Agriculture Faculty of Flores University, 2025)
Rice is one of the primary food crops that plays a vital role in improving the welfare of Indonesian society. However, crop failures often occur, one of which is caused by pathogen attacks. This study aimed to identify the types of pathogens affecting rice plants in Oesao Village, Kupang Timur District, Kupang Regency. The research was conducted from February to April 2024. Samples of diseased rice plants were collected from Oesao Village, while the isolation and identification processes were carried out at the Microbiology Laboratory, Faculty of Agriculture, Univesitas Nusa Cendana. The study utilized the diagonal sampling method by selecting five points within a paddy field and observing plants showing disease symptoms. Diseased plant parts were examined, photographed, sampled, and brought to the laboratory for pathogen isolation and identification. The results identified five types of pathogens infecting rice plants: Alternaria padwickii (causing circular leaf spots), Curvularia sp. (causing brown leaf spots), Drechslera oryzae (causing leaf spots), Fusarium oxysporum (causing stem spots), and Fusarium sambucinum (causing root rot). Interviews with farmers revealed that these pathogens significantly contribute to the decline in rice production in Oesao. These findings are crucial for developing pathogen control strategies in rice cultivation to enhance yield and food security in Indonesia, particularly in Oesao and its surrounding areas.